Strand 2: Structural Biology Courses on the Internet - Sansom, Clare; Driessen, Huub; Moss, David (Proceedings of the International Conference on Networked Learning, 1998)
During the next ten years, we envisage fundamental changes in the provision of higher education. Firstly, the widespread use of information technology will enable students to study whenever and wherever they wish. Secondly, the pace of technological change in society will require a workforce where lifelong learning is part of the culture. The era when students in higher education arc typically under 25, living away from home and studying full-time, must be coming to an end. The Internet is an important medium for the delivery of educational materials and, increasingly, complete courses. The Department of Crystallography at Birkbeck College, London, has been in the vanguard of these developments. For the past three years, we have been running an Advanced Certificate course entitled Principles of Protein Structure using the Internet [1,2] (subsequently referred to by the acronym PPS). This was one of the first tutorassisted, accredited, University level courses to be caught entirely over the Internet, and is certainly the first in biomolecular sciences in the UK. In 1997 it received an award from the Universities and Colleges Information Systems Association (UCISA) for innovative use of the World-Wide Web in higher education. This year a second Internet-based course, Advanced Certificate in Protein Crystallography on the Web2, acronym PX, was introduced. Both these courses are of twelve months’ duration and of final year undergraduate standard, although almost all their students are graduates. Successful students receive the award of an Advanced Certificate from London University, which is a graduate level qualification approximately equivalent to half a UK Master’s degree.